Wheat/wild relatives interspecific crosses to identify male fertility restorer factors in alloplasmic lines - Lavergne, Constance (2019)
Wheat is an important crop and represents an essential component of the global food security. Hybrid wheat, which currently occupies only a niche sector in commercial wheat production because of several barriers could help facing the challenges of a growing population and climate changes.